المباحث المشتركة بين اللغة وعلم الأصول في ضوء حاشية القطب الشيرازي: (Common Investigations Between Language and Etymology in Light of Hashiyah Al-Qutb Al-Shirazi’s) - Benabidi, Mohamed Tahar; Abdallah Abu-Alhaj, Thabet Ahmad; Ariffin, Sedek (Online Journal of Research in Islamic Studies, 2024)
This study aims to highlight the efforts of Imam Al-Shirazi in linguistic issues and matters that scholars have discussed in the field of Usul Al-Fiqh (Principles of Jurisprudence) through his commentary on Al-Zamakhshari’s interpretation. The personality of Al-Zamakhshari is controversial due to his opinions and interpretations. Scholars and researchers have examined his ideas and heritage through study, research, criticism, and commentary. This turned his book "Umdat Al-Nas fi Abwab Al-Lughah wal-Balaghah" into a subject of debate among them. Many scholars considered him as having a unique approach in addressing linguistic and rhetorical issues. Al-Shirazi is one of the prominent scholars in Usul and Furu’ (Branches of Jurisprudence) who took the initiative to enrich this interpretation with a valuable commentary, especially in the linguistic aspect. This study concluded the extent of Al-Shirazi’s interest in foundational linguistic discussions through both theoretical exposition and commentary, where his choices in these discussions were in line with the well-known opinions of scholars.